Analysis of Cost Of Goods Sold At A Profit The Pharmacy - Li Zhuo Zhen (International Journal of Economic Research and Financial Accounting, 2022)
This study entitled " Analysis of Cost of Goods Sold In Profit Pharmacy , with the formulation of the problem is : " Is the Price Determination of Sales At Has Earned Income Optimal ? "This study aims to determine the Price Determination of Sales and Profits What is optimal at Kimia Farma Pharmacy using Descriptive Analysis . The results showed that the calculation of cost of goods sold from 2013 through 2014 can be seen Profits not yet optimal because the sales targets set each year has not been reached . Profit decline that occurs due to declining prescription sales of credit and operational costs which did not experience significant differences.